The Optimal High Heating Value of the Torrefied Coconut Shells - Espina, R.; Barroca, R.; Abundo, M. L. S. (Engineering, Technology & Applied Science Research, 2022)
Coconut is a biomass resource that is abundant in tropical countries. In 2020, the Philippines planted 347 million coconut trees that produced 14.7 million tons of coconuts. The coconut shells (endocarp) are considered a waste material, which comprise 15.18% of each fruit and account for 2.2 million tons. The calorific value of raw coconut shells is 30.79MJ/kg. When torrefied at 275°C for 30 minutes holding time, the calorific value reached the optimal of 34.37MJ/kg, representing an increase of 11.64%. The mass yield (My) was 90.10% and the energy density was 111.64%, resulting in an energy yield of 100.59%.